Faktor yang Mempengaruhi Kesiapan Berwirausaha dan Leadership pada Siswa Sekolah Menengah Kejuruan - Yana Andayani; Nunung Nurjanah; Didik Dwi Prasetya (Jayapangus Press, 2023)
Along with the industrial revolution, society needs to prepare itself for the impact on all areas of life. One problem is that there is an abundance of labor but the use of artificial intelligence can fill certain sectors. Vocational high school graduates must have entrepreneurial readiness and leadership skills. This research aims to analyze the factors of fieldwork practices and creative and entrepreneurial product subjects on entrepreneurial readiness and leadership. This research is quantitative correlational type. 226 students from 6 vocational high school in Pasuruan Regency filled out a questionnaire with closed questions on a Likert scale. Data were analyzed descriptively and statistically with multiple linear regression tests. The influence of fieldwork practices and creative and entrepreneurial product subjects on entrepreneurial readiness each have a p-value <0.05. Likewise, fieldwork practices and creative product and entrepreneurship subjects on leadership each have a p-value < 0.05. The results of the analysis show that there is an influence of fieldwork practices and creative product and entrepreneurship subjects on entrepreneurial readiness and leadership skill.